EP966 Borderline ovarian tumours: a single institute retrospective study. (1st November 2019) - Rocha, AC; Sá, MI; Abrantes, C; Raposo, S; Sousa, R; Correia, P; Aldinhas, P; Branco, E; Coelho, C; Baltar, V; Sá, L
Abstract : Introduction/Background: Borderline ovarian tumours (BOT) are a group of ovarian epithelial tumours (OET) defined by atypical epithelial proliferation without stromal invasion. They represent 10–20% of all OET and have an excellent prognosis. Recurrence and malignant transformation can occur, however we still cannot predict which women will recur. Our aim is to determine the clinical, epidemiologic and histological features of the BOT. Methodology: A retrospective coorte study involving 79 patients diagnosed with BOT and treated at IPO-Coimbra between 1990–2016. Patients data was obtained from hospital records. Results: The average age was 50, 3 years. 24, 1% of the patients were <40 years. We included 25 mucinous tumors, 46 serous, 2 endometrioid, 3 seromucinous and 1 Brenner tumor. 88, 6% of them were in stage-I, 7, 6% in stage-II and 3, 8% were in stage-III. All patients had surgery as a primary treatment; in 32, 7% of the cases was performed a conservative surgery. Three patients were subjected to adjuvant chemotherapy. After a mean follow up of 5, 9 years, we reported 4 cases of relapse, 3 with malignant transformation to invasive ovarian cancer. 3 patients died during this period; the overall survival at 5 and 10 years was respectively of 100% and 96, 2%. Ca125, FIGO stage and peritoneal implants were associated to disease recurrence. Neither micropapillary growth pattern nor age showed that association. Conclusion: Our study reveal that the overall prognosis of BOT is good. Relapse cases were mainly related to FIGO stage and the presence of invasive peritoneal implants. Conservative surgery was not related with higher recurrence rate. Disclosure: Nothing to disclose.